Testing and analysis of axially loaded normal-strength recycled aggregate concrete filled steel tubular stub columns. (1st March 2015) - Wang, Yuyin; Chen, Jie; Geng, Yue
Highlights: Experiments on 39 RACFST stub columns. Scatter of the mechanical properties of RACFST stub columns. Influence of recycled aggregate replacement ratio on confinement effects. Model equations for steel tubes and RAC cores. Abstract: Thirty-nine stub columns were tested to failure to investigate the compressive behaviour of normal-strength recycled aggregate concrete filled steel tubular (RACFST) stub columns under axial loading. Study parameters included recycled coarse aggregate (RCA) substitution level, source of RCA, compressive strength of recycled aggregate concrete (RAC) core and ratio of steel area over concrete area. Experimental results showed that the scatter in the mechanical properties of RACFST stub columns is smaller than that in RACs due to the contribution of steel tubes. The source of RCA had little effect on the compressive behaviour of axially loaded RACFST stub columns within the parameter range adopted in the tested specimens. A reduction of less than 10% was measured in the compressive strength of RACFSTs due to the incorporation of RCA, which is smaller than that for RAC samples in material tests. As part of the work, confinement effects of the steel tubes to the RAC cores during the whole loading process were investigated based on the strain gauge measurements. Model equations were then proposed to predict the longitudinal stress–strain relationships for both steel tubes and RAC cores. Current CFST design provisions are compared with the RACFST stub columns test results, and the design recommendations are presented.